EFFECT OF ENRICHMENT BIOCHARE BY NITROGEN AND USED AS SLOW RELEASE FERTILIZER ON NITROGEN AVAILABILITY AND YIELD OF OKRA (Ablemoscus esculentus L. Moench) PLANT - Mohsin Abdulhay Desher; Zaineb Shahied Jasiem; Abdulamier Moaazi Mahmood (University of Thi-Qar Journal of agricultural research, 2022)
A greenhouse experiment was conducted in agricultural research station - College of Agriculture / Garmat Ali campus during the winter season 2020 - 2021 in Silty clay soil under drip irrigation system, cultivated Okra crop Ablemoscus esculentus L. Monech, Hasnawi variety local production, to study the effect of different levels of Biochar enrichment by nitrogen and used as slow release fertilizer on nitrogen availability in soil and yield of Okra plant. The study included an impact statement Iraqi urea fertilizer source of nitrogen (46 % N) as control and Biochar enrichment with nitrogen: (NECB %100), (NECB %75 + N %25), (NECB %50 + N%50), (NECB %25 + N%75). Fertilizers apply as soil application when preparation soil in greenhouse before planting seeds, the results of this study showed: The fertilizer of Biochar enrichment with 100% nitrogen (100% NECB) significantly superior on available nitrogen in soil by 23.28 gm Kg-1 at deep distance (0 - 25) cm deep and significantly superior of particle biochar size (2 mm) with15.33 gm Kg-1 respectively compared with other treatments during plant grown season. Also same treatment (100 % NECB) were significantly superior on total yield by values 8.12 ton ha-1 compared with other treatments during last period of plant growth respectively. * The research as a part of MSC thesis of first author.